PENERAPAN PIDANA PEMBINAAN DI LUAR LEMBAGA TERHADAP ANAK SEBAGAI BENTUK PIDANA DENGAN SYARAT - rahmithasari marwahputri; Syamsuddin Muchtar; Nur Azisa (JURNAL ILMIAH LIVING LAW, 2023)
This study was written to find out and analyze the application of criminal conditions on children who are perpetrators of crimes based on Decision Number 2/Pid.Sus-anak/2020/PN.SKG and the implementation of criminal coaching outside the institution against children in accordance with the form of criminal conditions with conditions. The results of the study show that there are efforts from law enforcement to protect the rights of children in conflict with the law. Coaching outside the institution also really requires coordination between the Community Counselor and the child's parents. There is a legal vacuum in terms of technical regulations for fostering children outside the institution. So that the Supervision of Children should be made technical implementing regulations so that they can be used as a reference by the Community Counselor in carrying out their main duties and functions.  Keywords : Criminal Conditions; Child; Coaching.